2012
DOI: 10.1002/chem.201103616
|View full text |Cite
|
Sign up to set email alerts
|

Design and Function of Pre‐organised Outer‐Sphere Amidopyridyl Extractants for Zinc(II) and Cobalt(II) Chlorometallates: The Role of CH Hydrogen Bonds

Abstract: Four new sterically hindered pyridines, L(1)-L(4)-containing amido substituents at the 2-position act as efficient solvent extractants for [CoCl(4)](2-) or [ZnCl(4)](2-) from acidic chloride solutions through protonation of the pyridino N-centre to form the neutral outer-sphere complexes [(LH)(2)MCl(4)]. These ionophores show very high selectivity for chlorometallate anions over chloride ion and are readily stripped to liberate the free-metal chlorides without the formation of inner-sphere complexes [ML(2)Cl(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 54 publications
1
28
1
Order By: Relevance
“…Aliphatic derivatives of b) have been described previously, 11 and those of the type c) are the subject of this paper.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Aliphatic derivatives of b) have been described previously, 11 and those of the type c) are the subject of this paper.…”
Section: Figurementioning
confidence: 99%
“…12 Ensuring that equilibrium (5) is favoured over (8) is a challenging target because this runs counter to the Hofmeister bias in which more highly charged anions, which have higher hydration energies, are expected to be more difficult to extract into low polarity water-immiscible solvents. 13 (8) Earlier work 11,15 has shown that a series of amidopyridines are strong chloridometalate extractants and show a high selectivity for ZnCl 4 2-over Cl -. They are readily stripped without the pyridine nitrogen atom entering the inner coordination sphere of the metal due to the bulky t-butyl substituents in the 6-position ( Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…The proligands L1H-L9H and L12H were prepared from the appropriate acetophenones (1-6) by conversion to the diketones (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and subsequent reaction with hydrazine. Details are provided in the ESI.…”
Section: Resultsmentioning
confidence: 99%
“…Pyridine-amides have been shown to be effective extractants for base metals such as Zn (II) and Co(II) [41,42]. In these systems, the number of amido-substiuents proximate to the pyridine is important to the selectivity of metalate over halide.…”
Section: Ion Pairs and Metalatesmentioning
confidence: 99%